Localization of brain lesions associated with disruption of smoking addiction - Köhler, Blanca (My University, 2024)
Substance addiction is a complex condition characterized by compulsive substance use, despite adverse consequences. Smoking addiction is one of the most common substance addictions in the world and a major risk factor for the development of many diseases, such as cardiovascular and pulmonary diseases, and certain types of cancer. Despite years of research, more effective treatments are still required. Lesion studies can be used to obtain causal evidence of the relationship between brain areas and behaviour. Previous lesion studies have found that occasionally stroke lesions, particularly insular lesions, can result in disruption of smoking addiction. This thesis aimed to investigate 1) whether cases of disruption of smoking addiction would be found in a large cohort of stroke patients, and 2) whether the lesion locations associated with disruption of addiction are more likely to involve the insular cortex or other specific brain regions. The study included 80 patients who had smoked pre-stroke. Patients identified as having experienced smoking addiction remission post-stroke were compared with the control group, which consisted of patients who continued smoking. The insular lesions were identified using volume of interest descriptives in MRIcroGL, and brain regions associated with smoking addiction remission were investigated using voxel-based lesion mapping (VLSM). Remission occurred in 21% of the patients, with variable lesion locations and no preference for the insula. No specific brain regions were significantly associated with disruption of addiction in the VLSM. This shows that brain lesions can modify addiction behaviour, but more research is needed to identify optimal treatment targets.
Keywords: smoking addiction, addiction, lesion study